GIL Top Policy Lessons on Empowering Adolescent Girls - World Bank (World Bank, Washington, DC, 2020)
Adolescent girls face multiple challenges that restrict their horizons, often having to make decisions about employment and their fertility at an early age, and with limited formal education opportunities. With lower levels of education than men, girls are often less equipped for work. Additionally, a plethora of expected domestic responsibilities limit their time for income-generating opportunities. A range of gender innovation lab (GIL) studies across Sub-Saharan Africa have demonstrated the potential of girls’ empowerment programs to change the life trajectories of young women even across a variety of contexts. These programs typically combine community-based girls clubs, life-skills training, vocational training, and sometimes financial literacy and microcredit access, for young women. In addition to implementation in countries such as Uganda and Tanzania, these programs have also helped create a buffer from conflict for young women in South Sudan and during the Ebola crisis in Sierra Leone - showing that they are beneficial even across fragile contexts.